FACING THE RELIGIOUS MULTICULTURALISM IN INDONESIA: MULTICULTURALISM WITH A RELIGIOUS CONTEXT - Dini Anggraheni (Jurnal CULTURE (Culture, Language, and Literature Review), 2022)
This study examines how multiculturalism has been theorized, implemented, and utilized in Indonesia as a policy, discourse, and practice. The post-Suharto (the 2nd President of Indonesia) democratic process has created fresh room for formerly suppressed identities to be expressed. While much of the research on multiculturalism concentrates on racial and ethnic differences, this article attempts to widen the term's definition to encompass religious differences, as well as assess the feasibility of "religious multiculturalism", especially in Indonesia. It responds to the following concerns: What are the perspectives on multiculturalism? What are the differences between multiculturalism and pluralism? How is diversity perceived and also implemented? What distinguishes the Western concept of multiculturalism from Indonesian concepts of variety, unity in diversity, and heterogeneity? This study uses qualitative research using library research and several scholars were used to enrich this study.